Case of step-by-step combined treatment of a patient with a ruptured aneurysm of the ophthalmic segment of the internal carotid artery - D. V. Litvinenko; E. I. Zyablova; V. V. Tkachev; G. G. Muzlaev (Сеченовский вестник)
Aneurysms of the internal carotid artery are the second most common among cerebral aneurysms. When an aneurysm is located in the ophthalmic segment of the internal carotid artery (ICA), the intravascular treatment method is a priority. At the same time, the treatment of recurrent and non-radially switched-off aneurysms of this localization remains a subject of discussion.Case report. We present a 42-year-old patient with a ruptured ICA aneurysm who was admitted in a serious condition. Initially, the patient underwent partial occlusion of the aneurysm cavity with endovascular coiling. In the control cerebral angiography 3 months after the haemorrhage, the recanalization of the aneurysm was verified, which served as an indication for repeated surgical intervention. We preferred the microsurgical method of treatment. A control angiographic study 1 year after the second operation confirmed the radical shutdown of the aneurysm.Discussion. The presented case illustrates the need for a flexible approach in the treatment of complex paraclinoid aneurysms. The choice of endovascular treatment of such aneurysms in the acute period of haemorrhage is justified as the most sparing, although less radical. Depending on the nature of the embolization performed, the timing of the control angiographic examination should be selected individually and can be reduced to 2 months. If there are indications for repeated surgical intervention, it should be performed by the safest method, providing total shutdown of the aneurysm and reducing the volumetric impact of the aneurysm dome on the optic nerve.